Heart rate variability in healthy adult dogs, and residents in hypobaric hipoxia (Bogotá, 2600 meters above sea level) - Guerrero S., Claudia Marcela (2024)
Heart rate variability (HRV) refers to beat-to-beat fluctuations in heart rate and represents the neurovegetative and endocrine influence on the heart. In the present study, HRV values were obtained in healthy adult canines of both sexes, residing in the city of Bogotá (2600 meters above sea level). Time-domain and frequency-domain HRV parameters were obtained using 60-minute Holter recordings. The distribution of the data was determined using the Shapiro-Wilk test. The dogs were distributed into two subgroups to study their behaviour in relation to sex and age. ANOVA and Kruskal Wallis tests were used to determine statistical differences. In general, the mean HRV values differ from those reported by other authors in studies at sea level and at lower altitudes. The differences in HRV in relation to sex were significant in the RMSSD and pNN50 parameters. There were no differences in the relationship between HRV and age.